UPAYA MENINGKATKAN KINERJA UMKM DI WILAYAH KECAMATAN WONOCOLO MELALUI KEGIATAN PENDAMPINGAN USAHA - Rachma Yulia, Novie Noordiana; Widodo, Agus Purbo; Putro, Suryati Eko; Indriawati, Arlisa; Rochana, Wahyu; Pribadhi, Agung (Komunitas Manajemen Kompetitif, 2024)
This report discusses community service activities to improve the performance of MSMEs in Wonocolo District through a participation-based mentoring program. This program is designed to overcome challenges such as low financial literacy, limited access to technology, and managerial capabilities with participatory methods that actively involve MSME actors. The approach includes needs analysis, training, individual mentoring, and monitoring and evaluation. As a result, 70% of participants started using social media and marketplaces for marketing, 60% diversified their products, and their managerial capacity improved. Although effective, challenges such as low digital literacy and mentoring time still require attention. Collaboration between the government, educational institutions, and local communities is needed to support the sustainability of this program to make MSMEs more competitive in local and regional markets.